ANALISIS KEPUASAN KONSUMEN PADA SPBU SHELL FATMAWATI II DKI JAKARTA - Aura Alshafa Yasmine (2023)
This study uses a quantitative method with the purpose to find out, prove, and analyze the influence of Product Quality, Service Quality, and Facilities on variable Consumer Satisfaction. This study used 100 respondents from consumers who already have made purchase transactions on Shell Fatmawati II Gas Station DKI Jakarta as primary data, and secondary data researchers obtained through various references related to research. Data were collected using purposive sampling technique and analyzed using descriptive and inferential analysis techniques with the help of SmartPLS 3.2.8 software. The respondents collected were 100 consumers of Shell Fatmawati II Gas Station. The results of the study show that the three factors, product quality, service quality and facilities, have a positive and significant impact on consumers satisfaction. The path coefficient value proves that product quality has an effect of 0.232, service quality of 0.511, and facilities has an effect of 0.246. The dominant factor that influences it is service quality of 0.511. The Adjusted R Square test result of 95,8% shows that the contribution of product quality, service quality and facilities variables together can represent the consumers satisfaction variable, while 4,2% is explained by other factors.